EFISIENSI FAKTOR-FAKTOR PRODUKSI USAHATANI SUSU SAPI PERAH DI KUD JATINOM KECAMATAN JATINOM KABUPATEN KLATEN JAWA TENGAH - Sri Jarwanta; Kusriani P Kusriani P; Subagyo ES Subagyo ES (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2012)
This research was carried out on February to April 2007. The aim of this research is to knowing the production factors, which is fluential to milk of cow, the efficiency of using production factors and the amount of the cost, revenue the benefit, and the income of milk cow operation. This Research location is executed in region of Jatinom of Sub-Province Klaten covering 4 countryside that is countryside mundu, countryside glagah, countryside kayumas, countryside bandungan by jumah is sampel 30 people of dairy cattle breeder. The main method used is analytical description and is the realization used survey method. The location determination with purposive, the determination of sample number of farm with proportional random sampling. The process of data collecting done by some interview with the farmers using questioner. The method of data analysis Cobb Douglas type, and efficiency analysis. Result of production analysis indicator using wide production (1) The factor production about total of livestock must still production very significant on milk production, and the decrease of cage, decrease of equipments, ransume, additional ransume, labour, education, and experience non significant on milk production (2) The efficiensy of production factors on total of livestock, decrease of cage, additional ransume, and labour shown not effiesien so that to increase for used. For the decrease of equipments, ransume, not efficient so that to decrease to used. ( 3) total Expense released by farmer of ox milk ofÂ year is equal to Rp 19.693.333, its acceptance equal to Rp. 37.896.600, earnings mean of is Rp 18.203.267.